Aplicação de sondagens elétricas verticais na estimativa da profundidade do embasamento cristalino nos municípios de São João de Pirabas e Salinópolis, Região Costeira do Nordeste do Pará - MONTEIRO, Daniele Pantoja (2018)
This work applies the electrical resistivity method, through vertical electrical soundings (VES) in the counties of São João de Pirabas and Salinópolis, both located in the northeastern costal region of the state of Pará. In this region, there are Miocene deposits, designated Pirabas and Barreiras Formations, the term Pirabas Formation being used for the carbonate sequence containing secondary interleaves of black to green shales and yellowish sandstones; and Barreiras Formation is used for the superimposed sedimentary united, characterized generically by siliciclastic deposits of variegated colors. In this work complementary geophysical information was added, for the project of paleoenvironmental and paleogeographic studies of the Pirabas Formation (Paleogenic-Neogene) and the main goal was to estimate the geological contact between the crystalline basement and the Pirabas Formation. The Wenner electrode arrays was chosen, due to the relative sensitivity of this type of array to vertical variations in apparent resistivity (horizontal structures) and the high signal-to-noise level ratio, which was of great importance to delimit the contrasts of apparent resistivity of the Barreiras, Pirabas sedimentary units and crystalline basement. Using vertical electrical sounding data was determined the subsurface resistivity values for different depths and correlating them whenever possible with geological information from drilled wells, available on the online platform of the Groundwater Information System (SIAGAS). The VES data was inverted using the IPI2win program (Geoscan-M Ltda) designed to perform automatic 1D inversion that provides important information about local geology, such as resistivity, depth, layer thickness and altimetry. In general, the results obtained with the electrical soundings showed that it is possible through the correlations of geophysical and geological of wells data, estimate the contact for the Barreiras and Pirabas Formations and the contact of the crystalline basement with the base of the Pirabas Formation. In addition, the method showed to be efficient in the identification of subterranean aquifers the same depth of the contacts between the Formations. The depths of the contacts between the Formations were 15 meters in São João de Pirabas and 5 meters in Salinópolis. While, the top of the crystalline basement is located around 38 meters deep in Salinópolis.